Transformasi Digital UMKM: Opencart Sebagai Srategi Promosi Kreatif Produk Home Industry di Kabupaten Sijunjung - Izzati Masyerli, Ghazia Atiqah; Annas, Firdaus; Mahendra, Andini (Yayasan Lembaga Studi Makwa, 2023)
This article aims to examine the use of OpenCart as a creative promotional strategy for home industry products in Sijunjung Regency. Home industry products in this area have good quality, but the promotional methods used are still traditional, such as direct marketing. This method is considered less effective for reaching a wider market, especially in the current digital era. It is hoped that the use of digital platforms such as OpenCart can be a more efficient and effective solution in marketing products online, making it easier to manage sales, expanding market reach, and opening up bigger business opportunities. This research uses a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. This research involved online interviews with six MSME owners in Sijunjung Regency who focused on two product categories, namely processed food and handicrafts. These interviews provide a clearer picture of marketing issues and their expectations regarding the use of digital platforms. The result of this research is the development of a website-based digital platform with features such as product catalogs, digital payments, order tracking, and social media integration. In this way, it is hoped that it can help local economic growth through marketing that is more creative and responsive to consumer needs. Apart from that, it is hoped that this platform can be an example for other MSMEs to utilize digital technology to increase competitiveness in a market that is increasingly competitive and developing rapidly in this digital era. This can also make a positive contribution to the regional economy by expanding markets and improving the overall welfare of society. With the hope, this digital technology will create bigger and more innovative business opportunities.